The Digital Transformation in Teaching Methods as the New Normal in Abu Dhabi Private Schools - DWEEDAR, LAIALI (2022)
The COVID-19 pandemic has given an unexpected boost to digital education in K-12 schools. This pandemic forced a rapid shift to digital learning and accelerated educational digital tools integration. Many educational institutions worldwide have offered online and blended learning programs, citing the benefits of flexibility, accessibility, innovation, and sustainability. In the post-COVID-19 pandemic, digital learning seems to be the best choice that plays a significant role in quality education. According to much research, Online learning will interact with traditional teaching to provide more options, enhance education equity, and promote innovation by merging artificial intelligence and mobile education. The study investigates the digital transformation in Abu Dhabi K-12 private schools during COVID19 and how this shifting to distance learning and using technology tools affects the teaching methods. It also discovers the best teaching methods and strategies teachers adopt to engage the students and enhance their learning. On the other hand, the study explores teachers’ perspectives on digital learning and schools’ leaders' perceptions of the future of K-12 education post-COVID-19. The target sample population of the study consists of teachers, two subjects’ coordinators, one Hod and one school principal from different private schools in Abu Dhabi. A mixed-methods data collection approach was applied to gather quantitative and qualitative data, including an online questionnaire and semi-structured interviews. The validity and reliability of the research tools were assessed carefully to verify that they were appropriate. The findings revealed that teaching methods had been changed from traditional to more flexible methods that fit the current COVID-19 crisis and beyond. The results also showed a positive teachers’ perception of Digital learning, which school leaders believe will continue with us as the new normal. Meanwhile, they found the blended or hybrid learning model as the most successful teaching, and learning model during and post Covid-19.